Zanubrutinib-induced aseptic meningitis: a case report and literature review - Yang, Jinjun; Wang, Lian; Zhong, Xiao; Yang, Chenlu; Wu, Yu (Frontiers in Pharmacology, 2023)
Zanubrutinib is a Bruton tyrosine kinase (BTK) inhibitor used in B cell malignancy treatment and is generally well tolerated in most patients. Zanubrutinib-induced aseptic meningitis is currently not reported. Herein, we present the first case of zanubrutinib-induced aseptic meningitis. A 33-year-old woman was diagnosed with relapsed/refractory follicular lymphoma and subsequently developed aseptic meningitis after receiving zanubrutinib treatment. We reviewed the literature and uncovered the lack of current reports on zanubrutinib or other BTK inhibitor-induced aseptic meningitis. Moreover, we summarized cases on aseptic meningitis induced by common chemotherapy and targeted drugs used for hematological diseases. Drug-induced aseptic meningitis (DIAM) is a drug-induced meningeal inflammation. The possible pathogenesis is the direct stimulation of the meninges via intrathecal injection of chemotherapy drugs and immune hypersensitivity response caused by immunosuppressive drugs. It is more common in women with immune deficiency and mainly manifests as persistent headache and fever. Cerebrospinal fluid examinations mainly demonstrate a significant increase in cells and proteins. DIAM diagnosis needs to exclude bacterial, fungal, viral, and tuberculosis infections; neoplastic meningitis; and systemic diseases involving the meninges. The prognosis of DIAM is usually favorable, and physicians should detect and stop the causative drug. In conclusion, zanubrutinib-induced aseptic meningitis is a rare but serious complication, and physicians should be promptly aware of this adverse event to avoid serious consequences.